Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/jnc.12196
|View full text |Cite
|
Sign up to set email alerts
|

The Parkinson's disease‐associated GPR37 receptor‐mediated cytotoxicity is controlled by its intracellular cysteine‐rich domain

Abstract: GPR37, also known as parkin‐associated endothelin‐like receptor (Pael‐R), is an orphan G protein‐coupled receptor (GPCR) that aggregates intracellularly in a juvenile form of Parkinson's disease. However, little is known about the structure or function of this receptor. Here, in order to better understand the functioning of this receptor, we focused on the GPR37 C‐terminal tail, in particular on a cystein‐enriched region. Thus, we aimed to reveal the role of these residues on receptor plasma membrane expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…In addition to the effects of prosaposin and prosaptide on astrocytes demonstrated in this paper, prosaptide and prosaposin have been shown to exert effects on Schwann cells (26,28,59), oligodendrocytes (26), and certain populations of neurons (30,38,41,60), cell types that are known to express significant levels of GPR37 and GPR37L1 (10,56). Furthermore, it is interesting to note that prosaptide and the invertebrate peptide HA, which has previously been reported to activate GPR37 (17,18), are similar in length and exhibit significant sequence similarity in their C-terminal regions (K-V-I-L for HA vs. K-E-I-L for prosaptide). HA does not seem to be a true ortholog of prosaptide, but nonetheless we propose that this invertebrate peptide may possess the ability to act as a GPR37 agonist owing to its similarity to prosaptide and prosaposin.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In addition to the effects of prosaposin and prosaptide on astrocytes demonstrated in this paper, prosaptide and prosaposin have been shown to exert effects on Schwann cells (26,28,59), oligodendrocytes (26), and certain populations of neurons (30,38,41,60), cell types that are known to express significant levels of GPR37 and GPR37L1 (10,56). Furthermore, it is interesting to note that prosaptide and the invertebrate peptide HA, which has previously been reported to activate GPR37 (17,18), are similar in length and exhibit significant sequence similarity in their C-terminal regions (K-V-I-L for HA vs. K-E-I-L for prosaptide). HA does not seem to be a true ortholog of prosaptide, but nonetheless we propose that this invertebrate peptide may possess the ability to act as a GPR37 agonist owing to its similarity to prosaptide and prosaposin.…”
Section: Discussionsupporting
confidence: 56%
“…Indeed, it has been reported that GPR37 can bind to a neuropeptide known as "head activator" (HA) (17,18), which is derived from the invertebrate Hydra. However, following a handful of reports three decades ago about the potential existence of an HA ortholog in mammalian brains (19,20), no further evidence for an HA ortholog in vertebrates has come to light.…”
mentioning
confidence: 99%
“…Previous reports have described prosaptide, a peptide fragment of prosaposin 25; 42; 43 , and the Hydra undecapeptide head activator (HA) 44; 45 as potential ligands of GPR37 and GPR37L1. To assess the signaling activity of GPR37L1 WT vs. the K349N mutant, induction of ERK phosphorylation was measured, as signaling from both GPR37 and GPR37L1 has been shown to stimulate ERK phosphorylation 25 .…”
Section: Resultsmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t Gandía et al 2014 GPR37 & tremulous jaw movement 6 We first evaluated the effect of GPR37 expression on tremor movements by comparing the number of pilocarpine-induced TJMs in WT and GPR37-/-animals. In both WT and GPR37-/-mice, the maximum number of TJMs was reached between 10 and 20 minutes after the administration of pilocarpine, while its effects were undetectable 1 hour later (Fig.…”
Section: Page 6 Of 16mentioning
confidence: 99%
“…It was first cloned in 1997 from human brain [2], but its function is still under debate. Thus, little information exists regarding this receptor, although some potential ligands have been recently proposed [3,4] and some structural information has been provided [5,6]. On the other hand, GPR37 has been postulated to play a role in certain pathologies, such as autism [7], depression and bipolar disorders [8], and more importantly in Parkinson's disease (PD).…”
mentioning
confidence: 99%